2018
DOI: 10.1210/en.2018-00020
|View full text |Cite
|
Sign up to set email alerts
|

Ovulatory Induction of SCG2 in Human, Nonhuman Primate, and Rodent Granulosa Cells Stimulates Ovarian Angiogenesis

Abstract: The luteinizing hormone (LH) surge is essential for ovulation, but the intrafollicular factors induced by LH that mediate ovulatory processes (e.g., angiogenesis) are poorly understood, especially in women. The role of secretogranin II (SCG2) and its cleaved bioactive peptide, secretoneurin (SN), were investigated as potential mediators of ovulation by testing the hypothesis that SCG2/SN is induced in granulosa cells by human chorionic gonadotropin (hCG), via a downstream LH receptor signaling mechanism, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
1
24
2
Order By: Relevance
“…However, the kinetics of progesterone production and normalcy of ovarian cycles suggest that may not be a significant factor in IR‐cKO mice. The putative role of TCF3 in relevant regulation of Scg2 is complicated as it is known to be regulated by LH, and we found that Lhcgr is downregulated in IR‐cKO ovaries. Thus, additional studies are required to verify the link between TCF3 and insulin signaling, and their intersection with FHS and LH signaling, but we believe TCF3 and its targets represent a potential new piece of the ovulation regulatory network worthy of further investigation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the kinetics of progesterone production and normalcy of ovarian cycles suggest that may not be a significant factor in IR‐cKO mice. The putative role of TCF3 in relevant regulation of Scg2 is complicated as it is known to be regulated by LH, and we found that Lhcgr is downregulated in IR‐cKO ovaries. Thus, additional studies are required to verify the link between TCF3 and insulin signaling, and their intersection with FHS and LH signaling, but we believe TCF3 and its targets represent a potential new piece of the ovulation regulatory network worthy of further investigation.…”
Section: Discussionmentioning
confidence: 83%
“…Another putative TCF3-regulated factor of relevance is Secretogranin II (SCG2), which is induced in granulosa cells during the periovulatory window. 48 The proteolytic cleavage product of SCG2 (SN peptide) is an established inducer of angiogenesis, 75 an essential process for ovulation and CL development and function in rodents and humans. 76,77 SN exhibited a dose-dependent effect on human ovarian endothelial cell sprouting, suggesting it can similarly promote angiogenesis in the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans, primates, and rodents treated with human chorionic gonadotropin (hCG) had enhanced ovarian tissue angiogenesis. hCG treatment is known to cause increased endothelial cell migration and vascular bud formation along with enhanced synthesis of proteins such as secretogranin II / (SCG2) and secretoneurin (SN) in the granulosa cells before ovulation ( Hannon et al ., 2018 ). It appears that hCG treatment increased the rate of angiogenesis in the groups offered ovarian stimulation in our study by increasing local vascular density and vascular area.…”
Section: Discussionmentioning
confidence: 99%
“…Although SN has been shown to be involved in many processes, including LH secretion and angiogenesis [ 97 ], the role of the other peptides is not fully understood as yet [ 98 ]. A recent study found that hCG induced upregulation in SCG2 mRNA levels in human, macaque monkey and rodents ovaries [ 99 ]. This study further showed that the SCG2 protein is localized in the theca, stroma and GCs in human and mice follicles and that its expression, in both species, is stimulated by hCG further demonstrating that SN significantly increased human ovarian microvascular endothelial cell migration.…”
Section: Ovulationmentioning
confidence: 99%